Recent advances of γ-aminobutyric acid: Physiological and immunity function, enrichment, and metabolic pathway - Heli, Zhou; Hongyu, Chen; Dapeng, Bao; Yee Shin, Tan; Yejun, Zhong; Xi, Zhang; Yingying, Wu (Frontiers in Nutrition, 2022)
γ-Aminobutyric acid (GABA) is a non-protein amino acid which naturally and widely occurs in animals, plants, and microorganisms. As the chief inhibitory neurotransmitter in the central nervous system of mammals, it has become a popular dietary supplement and has promising application in food industry. The current article reviews the most recent literature regarding the physiological functions, preparation methods, enrichment methods, metabolic pathways, and applications of GABA. This review sheds light on developing GABA-enriched plant varieties and food products, and provides insights for efficient production of GABA through synthetic biology approaches.